Remodelling the filtration bleb. Issue 8 (1st August 2002) - Morgan, J E; Diamond, J P; Cook, S D
Abstract : Aims: To report remodelling of enlarged dysmorphic filtration blebs with conjunctival compression sutures and autologous blood injection. Methods: A retrospective analysis of consecutively recruited patients with enlarged and dysmorphic filtration blebs who were managed with conjunctival compression sutures and subconjunctival autologous blood injections. Under topical anaesthesia, conjunctival (8.0-9.0 Nylon or 8.0 Vicryl) compression sutures were placed either side of blebs that were not showing signs of spontaneous resolution. In each case up to 0.75 ml of autologous blood was then injected into the areas of the bleb to be flattened. Supplemental injections of autologous blood were given in clinic as required. Results: In 11 eyes of 11 patients, conjunctival compression sutures were placed and autologous blood was injected, on average, 568 days following filtration surgery (range 41–2023). Supplemental autologous blood injections were required in eight patients, with three injections being given in one patient. In each case, the sutures were well tolerated and satisfactory compression of the conjunctiva was achieved. The highest intraocular pressure following injection was 25 mm Hg (mean 17.3, SD 4.2) and in none of the cases did blood enter the anterior chamber or parts of the filtration bleb bounded by the sutures. Conclusion: Conjunctival compression sutures with autologous blood provide a simple and effective means for remodelling the filtration bleb. The procedure can be performed under topical anaesthesia and does not hinder further bleb surgery, should this be required.